Thinking about sex work from a protagonist. A view over intimacies of a bar in southern Veracruz (Andamios, Revista de Investigación Social, 2016)
In this article, I hope to begin the lecture on the topics mentioned in the title of it, using as a starting point, some fragments of the life history of a subject of study and ethnographic data from that process. In this research observe a gender approach, daring to suggest a look at what “intimate” and the conversation analysis, that would allow me to examine the ways in which my subject of study, using their culture to be built as a woman and sex worker.
Keywords: Sex work; gender; intimacy; anthropology